2018
DOI: 10.1016/j.celrep.2018.07.105
|View full text |Cite
|
Sign up to set email alerts
|

Lin28 Signaling Supports Mammalian PNS and CNS Axon Regeneration

Abstract: SUMMARYRNA-binding proteins Lin28a/b regulate cellular growth and tissue regeneration. Here, we investigated the role of Lin28 in the control of axon regeneration in postmitotic neurons. We find that Lin28a/b are both necessary and sufficient for supporting axon regeneration in mature sensory neurons through their regulatory partners, let-7 microRNAs (miRNAs). More importantly, overexpression of Lin28a in mature retinal ganglion cells (RGCs) produces robust and sustained optic nerve regeneration. Additionally,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 57 publications
5
123
4
Order By: Relevance
“…1A). The fixed optic nerves were first tissue cleared to be transparent as previously described ( 12 ) and then axons were imaged with confocal microscopy. The results showed that very limited optic nerve regeneration occurred in wild type mice infected with AAV2-Cre.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1A). The fixed optic nerves were first tissue cleared to be transparent as previously described ( 12 ) and then axons were imaged with confocal microscopy. The results showed that very limited optic nerve regeneration occurred in wild type mice infected with AAV2-Cre.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study showed that overexpression of Lin28 in RGCs induced robust and sustained optic nerve regeneration via regulation of gene expression and enhanced intrinsic axon regeneration ability ( 12 ). Therefore, we tested if combining myosin IIA/B dKO, which alters axonal cytoskeletal dynamics, with Lin28 overexpression, which controls gene expression, could have combinatory promoting effect on optic nerve regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations